Strategi Pemasaran Kreatif Untuk UMKM Masyarakat di Lingkungan RW017, RW018, dan RW008 Perumahan Benda Baru Pamulang,Tangerang Selatan, Banten - Muhammad Adam; Dadin Tajudin; Dwi Setiawati; Marichicha Puicha L.Sinaturi; Daniel David Camberra Simanungkalit (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro,Small,and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, contributing more than 60% to the Gross Domestic Product (GDP) and absorbing nearly 97% of the workforce in the non-agricultural sector. However, MSMEs still face challenges in marketing and business management, particularly in leveraging digital technology. The Community Service Program (PKM) in Benda Baru Residential Area,South Tangerang,aims to enhance the knowledge and skills of MSME actors in designing and implementing creative, digital-based marketing strategies. This program includes training on SWOT analysis, digital marketing, and community-based marketing. The results of the program show an increase in the implementation of creative marketing strategies, such as the use of social media and digital platforms, as well as collaboration among business actors. This program is expected to have a positive impact on local economic development and streng then the digital business foundation in the region.